Social areas in Ljubljana - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
One of the most important research topics in social urban geography is spatial patterning and measuring of social difference and inequality. The main objective of the paper is to analyze and delineate the characteristics of social spatial segregation in Ljubljana. The research is based on an analysis of data from the 2011 population census. The basic method used was an analysis of the socio-economic, ethnic and family segregation of population on the territory of the Ljubljana Urban Municipality based on a comparison of the share of selected population groups in the former local communities.
Keywords: družbena neenakost; Ljubljana; mesta; prebivalstvo; socialna geografija; urbana geografija